Temperatur Sistem Pendingin Siklus Kompresi Uap Terhadap Perubahan Beban Pendinginan Dengan Penambahan Kondensor Dummy Sebagai Water Heater - Ginting, Hardianto; Aziz, Azridjal; Kurniawan, Iwan (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
The vapor compression cycle of air conditioning has been used as conditioner in a room to get comfort condition. Conditioning air happened because the heat on room was absorped by evaporator (indoor unit). Usually, heat on condenser will be discarded. The wasted energy in condensor can be used as hot water by adding dummy condenser as complement. The dummy condensor would influence the cooling system temperature of compression cycle with change of cooling load in this research. This research was done experimentally. The result of experiment showed that temperature was about 61.70 0C for 120 minutes in performance. When cooling load was given to room, refrigerant temperature would get higher so that temperature of hot water would be higher too.Keywords : Air conditioning, water heater, dummy condensor, cooling load.